Effectiveness of Ricinus communis as Natural Larvicide for Aedes aegypti Mosquito Larvae in Medan City - Chahaya, Indra; Tumanggor, Winni R.E.; Gultom, Evi Depiana (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Dengue Hemorrhagic Fever, a disease caused by Aedes aegypti, can be prevented by reducing larval density using natural larvicides. This research aimed to investigate the natural larvicide effectiveness in reducing the Aedes aegypti larvae density in Medan City in 2023. This quasi-experimental research conducted a pre-test and post-test on the Container Index (CI). The population in this study was 1,057 houses in Ladang Bambu Village, the sample being 150 houses. The treatments were control and Ricinus communis-seed powder at 40 mg, 80 mg, 100 mg, and 120 mg/l doses in ovitraps, placed next to the water reservoir. Consider specifying the unit of measurement for the container index. The container index was calculated before (day 0) and after treatment (day 7). Data were analyzed using paired T-test, one-way ANOVA, and LSD. The results were that the modified ovitrap with the seed of Ricinus communis was effective in reducing the Aedes aegypti mosquito larvae density. The analysis showed a significant difference in the mean CI between the control and the modified ovitrap, the most effective dose in reducing CI being 100 mg/l of water. The community can use the 100 mg/l seed of Ricinus communis in ovitraps as an eco-friendly vector control.